Characterization of a compact low cost 6.5kV Cockcroft voltage multiplier - Madhu Palati; Prashanth Narayanappa Ananda (Institute of Advanced Engineering and Science, 2022)
Generation of high voltages is often necessary in Industrial, Medical, civilian and defense applications. One of the popular methods of generation of high voltage DC is using a Cockcroft voltage multiplier generator. Knowledge on characterization of the voltage multiplier circuit helps the designer to study the effect of various input parameters on output, saves lot of time and money. In this paper various methods of generation of high voltages, advantages and disadvantages of each method are discussed. Design of five stage voltage multiplier circuit, fabrication and characterization of the 6.5kV voltage multiplier generator are presented. Simulation was carried using PSPICE software under different load conditions. Effect on the output voltage, ripple voltage with different values of load, frequency was studied. Experiments were carried out on the proposed prototype model and validated by comparing the values obtained from experimentation with the simulation and theoretical values